Detection of Hematopoietic Stem Cell Transcriptome in Human Fetal Kidneys and Kidney Organoids Derived From Human Induced Pluripotent Stem Cells - Hwang, Jin Wook; Desterke, Christophe; Loisel-Duwattez, Julien; Griscelli, Frank; Bennaceur-Griscelli, Annelise; Turhan, Ali G. (Frontiers in Cell and Developmental Biology, 2021)
Background In mammalians, hematopoietic stem cells (HSCs) arise in the dorsal aorta from the hemogenic endothelium, followed by their migration to the fetal liver and to the bone marrow. In zebrafish, the kidney is the site of primary hematopoiesis. In humans, the presence of HSCs in the fetal or adult kidney has not been established. Methods We analyzed the presence of HSC markers in the human fetal kidneys by analysis of single-cell datasets. We then analyzed in kidney organoids derived from induced pluripotent stem cells (iPSCs) the presence of hematopoietic markers using transcriptome analyses. Results Twelve clusters were identified as stromal, endothelial, and nephron cell type-specific markers in the two fetal stage (17 weeks) kidney datasets. Among these, the expression of hematopoietic cells in cluster 9 showed an expression of primitive markers. Moreover, whole transcriptome analysis of our iPSC-derived kidney organoids revealed induction of the primitive hematopoietic transcription factor RUNX1 as found in the human fetal kidney cortex. Conclusion These finding support the presence of cells expressing HSC transcriptome in the human kidney. The mechanisms of the appearance of the cells with the same transcriptional features during iPSC-derived kidney organoid generation require further investigation.